AB1195 Development and validation of an ultrasonographic activity score (USAS) for rheumatoid arthritis. (12th June 2018) - De Agustín, J.J.; Erra, A.; Ponce, A.; Moragues, C.; Diaz, C.; Moya, P.; Reina, D.; Estrada, P.; Casado, E.; Moreno, M.; ramirez, J.; Mateo, L.; et al.
Abstract : Background: Composite scores developed in Rheumatoid arthritis (RA) not include all dimensions of disease activity. An index based on essential clinical plus a ultrasound (US) measures, focused on simplicity, with appropriate validation, would allow a better classification at different levels of disease activity than a clinical only or US only index. Objectives: To develop and validate a mixed clinical-US inflammation score in RA for use in clinical practice. Methods: Mixed methods. Experts elicited items reflecting inflammation which were prioritised by Delphi. Patients with RA with various grades of activity underwent clinical [28 swollen and tender joints counts, patient and physician global assessment (PhGA), erythrocyte sedimentation rate, and C-reactive protein (CRP)] and US assessments [synovitis or tenosynovitis by grey-scale (GS) and Power Doppler (PD) of 42 structures], blinded to the clinical assessment. An index was created after supported selection of US structures and scoring method. Construct validity was tested by correlation with DAS28, SDAI, CDAI, and PhGA. Reliability was evaluated in a subgroup of patients with the intraclass correlation coefficient (ICC). Results: US of joints and tendons, CRP, and swollen joints were the items that passed the prioritisation phase. Then, 281 patients were randomly divided into design (n=141) and validation analysis (n=140). The combination of US sites chosen detected the maximum proportion of GS and PD present. Were elected wrist, 2–3 MCP, Knee, tibio-talar and 2–3 MTP joints, and the following tendons: carpal extensor and flexor tendons, tibial posterior and peroneal. For scoring structures, three methods were tested: semiquantitative (0–3 GS +0–3 PD), dichotomous (0/1 GS +0/1 PD), and qualitative (0/1 based on algorithm [image 1]). All showed strong correlation with activity measures (rho ≥0.60), and reliability (ICC 0.89 to 0.93). The most feasible index, qualitative, was chosen. The proposed formula for USAS was: USAS=N° swollen joints+US score+CRP Conclusions: USAS is a valid and reliable measure of inflammation in RA equal to the sum of 28 swollen joint count, a simplified (0/1) US assessment of 11 structures and CRP. Disclosure of Interest: None declared